Application of DPC and DPC-GA to the dual-rotor wind turbine system with DFIG - Benbouhenni, Habib (Institute of Advanced Engineering and Science, 2021)
The work presents the dual-rotor wind energy conversion system (DRWECS) with a direct driven doubly-fed induction generator (DFIG). The system consists of a dual-rotor wind turbine (DRWT) with a DFIG, the grid side converter (GSC), and the machine side converter (MSC). To command the MSC, the direct power command (DPC) based on genetic algorithm (GA) and classical pulse width modulation (PWM) has been applied. To achieve the maximum power from the DRWT, the maximum powe point tracking (MPPT) technique has been used. The performed simulation studies confirmed the high performances of the DPC-GA contro method.